Ant-aphid mutualism: the influence of ants on the aphid summer cycle - Tegelaar, Karolina; Hagman, Mattias; Glinwood, Robert; Pettersson, Jan; Leimar, Olof (Oikos, 2012)
There are few longtime studies on the effects on aphids of being tended by ants. The aim of this study is to investigate how the presence of ants influences settling decisions by colonizing aphids and the post-settlement growth and survival of aphid colonies. We conducted a field experiment using the facultative myrmecophile Aphis fabae and the ant Lasius niger. The experiment relied on natural aphid colonization of potted plants of scentless mayweed Tripleurospermum perforatum placed outdoors. Ants occurred naturally at the field site and had access to half of the pots and were prevented from accessing the remainder. The presence of winged, dispersing aphids, the growth and survival of establishing aphid colonies, and the presence of parasitoids were measured in relation to presence or absence of ants, over a period of five weeks. The presence of ants did not significantly influence the pattern of initial host plant colonization or the initial colony growth, but ant-tended aphids were subject to higher parasitism by hymenopteran parasitoids. The net result over the experimental period was that the presence of ants decreased aphid colony productivity, measured as the number of winged summer migrants produced from the colonized host plants. This implies that aphids do not always benefit from the presence of ants, but under some conditions rather pay a cost in the form of reduced dispersal.